Analisis Teknik Permainan Instrumen Flute pada Lagu Concertino for Flute Oleh Hayley Miller Pada pertunjukan Boston Philharmonic Youth Orchestra - Asmon, Shafira Permata Dewi; Widiastuti, Uyuni (Universitas Sultan Ageng Tirtayasa, 2024)
The aim of this research is to: 1) Describe the technical analysis of playing the flute instrument in the song Certino for Flute by Hayley Miller. 2) Describe the interpretation of the song Concertino for Flute by Hayley Miller at the